THE USE OF ARTIFICIAL INTELLIGENCE IN DEVELOPING STUDENTS’ CREATIVE THINKING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The rapid advancement of artificial intelligence (AI) technologies has significantly transformed modern education. This article explores the role of AI in fostering creative thinking among students. It examines theoretical foundations of creativity, identifies key AI tools used in educational settings, and analyzes their impact on students’ ability to think critically and innovatively. The study highlights both the opportunities and challenges associated with integrating AI into the learning process. The findings suggest that AI can serve as a powerful catalyst for creativity when used thoughtfully and pedagogically.